CORRELATION OF MOTHER'S EATING BEHAVIOR DURING PREGNANCY WITH THE TODDLER’S EATING BEHAVIOR - Rahmah Fadhilah Asrifqa; Meivita Dewi Purnamasari; Eni Rahmawati (International Journal of Biomedical Nursing Review, 2024)
Background: Toddler age is a golden period in the growth and development of children. One of the factors that inhibit children's growth and development is poor eating behavior. The child's eating behavior begins to be formed since the prenatal period through the transmission of amniotic fluid containing volatile compounds derived from food consumed by the mother during pregnancy. Purpose: This study aimed to analyze the relationship between maternal eating behavior during pregnancy with eating behavior in toddlers (1-3 years old). Methodology: Correlational analytic research with cross sectional research design. The total sample size was 101 mother and child respondents in Grendeng and Sumampir Villages, Purwoketo Utara II District. Data were collected using the AEBQ questionnaire for data on eating behavior of mothers during pregnancy and CEBQ-T for data on eating behavior of toddlers. Test the analysis of the relationship between the two variables used the pearson correlations. Result: The results of statistical tests showed a p-value of 0.001 (<0.05) with an r value of 0.552, which means that there was a significant relationship between the maternal eating behavior during pregnancy and the eating behavior of toddlers with moderate relationship strength. Conclusion: There was significant relationship between the maternal eating behavior during pregnancy and the eating behavior of toddlers (1-3 years).